Global energy shifts : fostering sustainability in a turbulent age - Podobnik, Bruce, 1968- (Temple University Press, 2006)
In the latter part of the nineteenth century, the citizens of Great Britain faced a formidable challenge: coal resources seemed destined to run out and commentators were unable to foresee a viable alternative fuel. To address the crisis, military strategists were urged to seize control of coal in foreign lands, and companies were encouraged to increase domestic production of the resource. In Global Energy Shifts, Bruce Podobnik draws intriguing parallels between the ""coal panics"" that once swept through Britain and the ""oil panics"" that grip the world today. His concis.